Continuous Learning to Optimize Competitiveness of the Administrative Staff of National University of San Marcos - Ugarte Casafranca, Walter David (2017)
The cultural change that we have been experiencing in recent decades, and the acquisition of much faster and reliable technologies, it requires that public officials properly processed such information. The emergence and growing importance of knowledge as a new production factor makes the development of technologies, methodologies and strategies for its measuring, creation and diffusion into one of the main priorities of the organizations in our societies. It is therefore necessary to ascertain the impact of these new tools in the job performance of staff who is responsible for the administration of public educational institutions.This study presents the current conditions of human talent management at the National University of San Marcos.